2008
DOI: 10.1038/jp.2008.113
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced kangaroo mother care for heel lance in preterm neonates: a crossover trial

Abstract: Objective: To test if enhancing maternal skin-to-skin contact, or kangaroo mother care (KMC) by adding rocking, singing and sucking is more efficacious than simple KMC for procedural pain in preterm neonates.Study Design: Preterm neonates (n ¼ 90) between 32 0/7 and 36 0/7 weeks' gestational age participated in a single-blind randomized crossover design. The infant was held in KMC with the addition of rocking, singing and sucking or the infant was held in KMC without additional stimulation. The Premature Infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 33 publications
1
48
1
13
Order By: Relevance
“…This position in practical use intensifies parent-child relationship [8] , has influence on breast-feeding behavior [9] , and neurological development [10] , is no barrier for phototherapy [11] , may decrease pain reception [12][13][14][15][16][17] , and in one study was shown to reduce blood transfusions [18] . Therefore, 90% of neonatal intensive care units in Germany apply SSC [19] .…”
Section: Introductionmentioning
confidence: 99%
“…This position in practical use intensifies parent-child relationship [8] , has influence on breast-feeding behavior [9] , and neurological development [10] , is no barrier for phototherapy [11] , may decrease pain reception [12][13][14][15][16][17] , and in one study was shown to reduce blood transfusions [18] . Therefore, 90% of neonatal intensive care units in Germany apply SSC [19] .…”
Section: Introductionmentioning
confidence: 99%
“…71 Bunun yanında, morbiditeyi ve mortaliteyi azaltması erken dönemde aileyi bebeklerinin bakımına katarak, aileyi ve özellikle anneyi ve anne-bebek ilişkisini güçlendirebildiği, emzirmeyi olumlu etkilediği için düşük doğum ağırlıklı bebeklerde konvansiyonel yenidoğan bakımına alternatif olarak önerilmektedir. 72,73 Term ve preterm bebekler ve ebeveynlerinin de ilk değerlendirmeleri yapıldıktan sonra kanguru bakımına 24 saat içerisinde başlanabilir. 74 Kanguru bakımı için ebeveynin giysilerinin bebeği sıcak tutacak özellikte yeterli genişlikte olması yeterlidir.…”
Section: Kanguru Bakımıunclassified
“…Entre as intervenções não farmacológicas, incluem-se o uso de substâncias adocicadas por via oral, do tipo sacarose Stevens et al, 2005), glicose (Chermont, 2008;Gradin & Schollin, 2005) e frutose (Akçam, 2004), a sucção não nutritiva (Stevens, Yamada, & Ohlsson, 2001), o contato pele-apele (Castral, Warnock, Leite, Haas, & Scochi, 2008;Chermont, 2008) e o Método Canguru (Johnston et al, 2009). As intervenções não-farmacológicas para o alívio de dor podem trazer grande benefício ao bebê hospitalizado e têm a sua eficácia comprovada, não apresentando riscos e tendo baixo custo operacional.…”
Section: O Contexto Inicial Do Desenvolvimento E a Dor Em Bebês Nasciunclassified